Avaliação econômica da alimentação de tilápias em tanques-rede com níveis de proteína e energia digestíveis - Koch, João Fernando Albers; Esperancini, Maura Seiko Tsutsui [UNESP]; Barros, Margarida Maria [UNESP]; Carvalho, Pedro Luiz Pucci Figueiredo de [UNESP]; Fernandes Junior, Ademir Calvo [UNESP]; Teixeira, Caroline Pelegrina [UNESP]; Pezzato, Luiz Edivaldo [UNESP] (Inst Pesca, 2014)
We evaluated the economic responses of Nile tilapia in the final stage (450 to 800 g) fed diets containing five levels of digestible protein (DP): 20, 23, 26, 29 and 32% and two digestible energy levels (DE): 3,000 and 3,300 kcal kg(-1) based on the sale of whole animals or fillet. This experiment was carried out into 50 m(3) net cages in an aquaculture area located in Paranapanema River, Palmital - Sao Paulo State, Brazil, from November 21st, 2010 to January 21st. Economic performance indicators were: gross revenue, partial production cost, net revenue, leveling point, balance point, benefit cost ratio and cost of feed kg(-1) gain. Twenty-nine percent of DP and 3,000 kcal DE kg(-1) diet provided better economic performance for sale of whole fish, meaning higher net revenue (R$ 23.09 net cage(-1)) and benefit cost ratio (1.08), besides the lowest balance point (R$ 3.91 kg-1). Thirty-two percent of DP and 3,000 kcal DE kg-1 diet provided the lowest cost of feed kg(-1) (R$ 2.53), leveling point (17.35 kg net cage(-1)) and balance point (R$ 13.63 kg(-1)), besides the highest benefit cost ratio (1.54) when the fish were sold in fillet form. Diets with 29% and diet with 32% digestible protein, both of them with 3,000 kcal of digestible energy kg(-1) diet provides better economic responses in Nile tilapia reared in net cages (450 to 800 g), to be sold, respectively, whole or fillets form.

Avaliaram-se as respostas econômicas da produção de tilápia-do-nilo na fase de terminação (450 a 800 g), alimentadas com dietas contendo cinco níveis de proteína digestível (PD): 20, 23, 26, 29 e 32% e dois de energia digestível (ED): 3.000 e 3.300 kcal kg-1 de dieta, com base na venda de animais inteiros ou filés. A pesquisa foi conduzida em 50 tanques-rede (1 m3), em área aquícola localizada no rio Paranapanema, Palmital-SP, Brasil, de 21 de novembro de 2010 à 21 de janeiro de 2011. Os indicadores de desempenho econômico calculados foram: receita bruta, custo de produção parcial, receita líquida, ponto de nivelamento, ponto de equilíbrio, relação benefício custo e custo da ração kg-1. A dieta contendo 29% de PD e 3.000 kcal de ED kg-1 proporcionou melhor desempenho econômico para venda de peixes inteiros, ou seja, maior receita líquida (R$ 23,09 tanque-rede-1) e relação benefício custo (1,08), além do menor ponto de equilíbrio (R$ 3,91 kg-1). A dieta com 32% de PD e 3.000 kcal de ED kg-1 possibilitou para a venda de filés o menor custo da ração kg-1 (R$ 2,53), menor ponto de nivelamento (17,35 kg tanque-rede-1) e de equilíbrio (R$ 13,63 kg-1), além da mais alta relação benefício custo (1,54). A dieta contendo 29% e a dieta contendo 32% de proteína digestível, ambas com 3.000 kcal de energia digestível kg-1 proporcionam melhores respostas econômicas de tilápias-do-nilo recriadas em tanques-rede (450 a 800 g), ao serem vendidas, respectivamente, inteiras e na forma de filés.
Economic analysis of feeding tilapia in cages with digestible protein and energy levels
Keywords: Production cost; Fish nutrition; Oreochromis niloticus; Gross revenue; Benefit cost ratio; Custo de produção; Nutrição de peixes; Oreochromis niloticus; Receita bruta; Relação benefício custo